2014
DOI: 10.1159/000362208
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Radiation Therapy and Bullous Pemphigoid

Abstract: Background: Bullous pemphigoid (BP) is an autoimmune subepidermal blistering disease. Objective: To review the literature on radiation therapy (RT)-associated BP. Methods: A review of the English language literature on patients who developed BP during and up to 10 years post RT was performed. Results: 29 patients were reported. 25 (86.2%) were women, 84% of whom had received RT for breast cancer. Three patients were male (10.3%). Gender was not mentioned in 1 (3.4%). 72% developed BP post RT; 28% developed BP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
76
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(81 citation statements)
references
References 40 publications
0
76
1
Order By: Relevance
“…Nguyen et al have summarized 29 patients with BP following radiation for malignancy treatment. BP was localized on the irradiated area in 25 of them, in two it was localized in non-irradiated sites and in another two it was generalized (44). All cases had a rather benign course, with corticosteroids being sufficient to control the disease.…”
Section: Discussionmentioning
confidence: 96%
“…Nguyen et al have summarized 29 patients with BP following radiation for malignancy treatment. BP was localized on the irradiated area in 25 of them, in two it was localized in non-irradiated sites and in another two it was generalized (44). All cases had a rather benign course, with corticosteroids being sufficient to control the disease.…”
Section: Discussionmentioning
confidence: 96%
“…9 According to a study by Nguyen and Coll, LBP develops in 72% of cases within six months after the end of radiotherapy and in 28% of cases during radiotherapy. 10 The appearance of LBP on the mouth after radiotherapy against laryngeal carcinoma has also been described. 11 The pathogenic mechanism of LBP development associated with radiotherapy is difficult to prove and remains hypothetical.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, Nguyen, Kwan, and Ahmed () reviewed the literature and reported the cases of 29 patients who developed bullous pemphigoid (BP) after receiving radiation therapy for cancer treatment. The relationship between onset of BP and time of radiation revealed that 72% of patients developed BP some months after the last cycle of radiotherapy.…”
Section: Discussionmentioning
confidence: 99%